2005
DOI: 10.1667/rr3373
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Lung Cancer and Leukemia from Exposure to Ionizing Radiation and Potential Confounders among Workers at the Portsmouth Naval Shipyard

Abstract: Significantly elevated lung cancer deaths and statistically significantly positive linear trends between leukemia mortality and radiation exposure were reported in a previous analysis of Portsmouth Naval Shipyard workers. The purpose of this study was to conduct a modeling-based analysis that incorporates previously unanalyzed confounders in exploring the exposure-response relationship between cumulative external ionizing radiation exposure and mortality from these cancers among radiation-monitored workers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…This study also adjusted for exposure to benzene, which was not feasible in the 15-country study. Recent estimates of radiation-associated risk within the PNS cohort (8,25) are somewhat higher than those observed in this study but are consistent with the rate ratio modification by facility shown in Table 5.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study also adjusted for exposure to benzene, which was not feasible in the 15-country study. Recent estimates of radiation-associated risk within the PNS cohort (8,25) are somewhat higher than those observed in this study but are consistent with the rate ratio modification by facility shown in Table 5.…”
Section: Discussionsupporting
confidence: 88%
“…Current cigarette smokers were defined as workers who were smoking cigarettes as of their cutoff date or workers who quit smoking 5 or fewer years prior to their cutoff date. For the 54% of workers with insufficient smoking history information, smoking status was imputed based on the socioeconomic status associated with the first job title (25), refined to reflect average smoking histories for a given job from survey data collected in the 1950s to 1980s (26). These assignments were validated using the relation between job titles and smoking history information for workers with complete information.…”
Section: Smoking Statusmentioning
confidence: 99%
“…The risk estimate for this study (within this meta-analysis) is benzene-adjusted. Other worker-based studies, particularly those based on more recent employment, have found little evidence of potential benzene exposures, as this substance was never used or has been phased out of many workplaces 29 40. Unlike solid cancers, leukaemia is advantageous for meta-analysis because it is not strongly associated with lifestyle factors, although there is some evidence of a moderate association (RR=1.4–2.0) between smoking and some leukaemias 57–59.…”
Section: Limitationsmentioning
confidence: 99%
“…Epidemiological studies among shipyard workers have been performed in many countries (Kolonel et al 1985;Krstev et al 2007;Nicholson et al 1980;Puntoni et al 2001;Yiin et al 2005), and health problems caused by asbestos exposure have been reported.…”
Section: Introductionmentioning
confidence: 99%